Energy Analysis of Contention Tree-Based Access Protocols in Dense Machine-to-Machine Area Networks. (22nd April 2015) - Vázquez-Gallego, Francisco; Alonso, Luis; Alonso-Zarate, Jesus
Abstract : Machine-to-Machine (M2M) area networks aim at connecting an M2M gateway with a large number of energy-constrained devices that must operate autonomously for years. Therefore, attaining high energy efficiency is essential in the deployment of M2M networks. In this paper, we consider a dense M2M area network composed of hundreds or thousands of devices that periodically transmit data upon request from a gateway or coordinator. We theoretically analyse the devices' energy consumption using two Medium Access Control (MAC) protocols which are based on a tree-splitting algorithm to resolve collisions among devices: the Contention Tree Algorithm (CTA) and the Distributed Queuing (DQ) access. We have carried out computer-based simulations to validate the accuracy of the theoretical models and to compare the energy performance using DQ, CTA, and Frame Slotted-ALOHA (FSA) in M2M area networks with devices in compliance with the IEEE 802.15.4 physical layer. Results show that the performance of DQ is totally independent of the number of contending devices, and it can reduce the energy consumed per device in more than 35% with respect to CTA and in more than 80% with respect to FSA.